Analisis Regresi Liner untuk Meramalkan Jumlah Siswa Sekolah Dasar di Cilacap - Aspriyani, Riski; Muhassanah, Nur'aini (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2024)
This research aims to determine a prediction model using Simple Linear Regression for time series data on the number of elementary school students in Cilacap from 2010 to 2023 and to obtain predicted results on the number of elementary school students in Cilacap for the following year. The data pattern of the number of elementary school students in Cilacap is known to have a decreasing trend. The time series data was subjected to the Durbin-Watson test to see whether there was autocorrelation. It was found that data on the number of elementary school students in Cilacap from 2010 to 2023 did not have autocorrelation with the Durbin-Watson (d) computing value of 1.385. The requirements for time series data have been met, so that forecasting analysis can be carried out using Simple Linear Regression and it is found that the regression equation is y ̂=168698.604-1600.519x. This regression equation is used to predict the value of the number of elementary school students in Cilacap for the next year. The forecasting accuracy level is 97.303% or with a MAPE error value of 2.697%, which means that the ability of the regression model to predict is very accurate. Thus, the predicted data on the number of elementary school students in Cilacap for the next period in 2024 is 144690 students. Keywords: Forecasting, Time Series, Linear Regression